Pengaruh Profitabilitas dan Ukuran Perusahaan Terhadap Pengungkapan CSR dengan Islami Sosial Reporting Indeks (Studi Empiris Pada Jakarta Islamic Index) - Marheni, Marheni (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2018)
The objectives of this study included: a) To analyze the effect of profitability on ISR disclosures; b) To analyze the effect of company size on ISR disclosures; c) To analyze the effect of profitability, firm size, on ISR Disclosure simultaneously. The population in this study are all companies listed in the Jakarta Islamic Index (JII) for the 2014-2016 period. The variables used in this study include Dependent variable (Y) is Islamic Social Reporting (ISR) (Y) and the independent variable (X) is profitability (X1) and firm size (X2). The method of data analysis uses descriptive statistical analysis and multiple linear regression analysis. Haisl research shows that profitability has a statistically significant effect on ISR, meaning that any increase or decrease in profitability affects the increase in ISR; the size of the company statistically has no effect on ISR, meaning that any increase or decrease in the variable size of the company has no effect on the increase and decrease in ISR.